With faith in God and heart and mind : a history of Omega Psi Phi Fraternity - Hobson, Maurice J.; Cole, Eddie Rice, II; Harper, Jim C.; Alridge, Derrick P. (Chapel Hill : The University of North Carolina Press, 2025)
When Edgar A. Love, Oscar J. Cooper, Frank Coleman, and Ernest Everett Just founded the historically Black fraternity Omega Psi Phi on November 17, 1911, at Howard University, they could not have known how great of an impact their organization would have on American life. Over the 110 years that followed, its members led colleges and universities; served in prominent military roles; made innumerable contributions to education, civic society, science, and medicine; and at least one campaigned for the US presidency. This book offers a comprehensive, authoritative history of the fraternity, emphasizing its vital role through multiple eras of the Black freedom struggle. The authors address both the individual work of its membership, which has included such figures as Carter G. Woodson, Bayard Rustin, Roy Wilkins, James L. Farmer Jr., Benjamin Elijah Mays, James Clyburn, Jesse Jackson, and Benjamin Crump, and the collective efforts of the fraternity's leadership to encourage its general membership to contribute to the struggle in concrete ways over the years. The result is a book that uniquely connects the 1910s with the present, showing the ongoing power of a Black fraternal organization to channel its members toward social reform.--
We will build a fraternity: intellectual foundations, 1909-1920 -- An unusual emphasis on scholarship: the success and challenge of expanding Black education opportunity, 1920-1929 -- Through days of joy or years of pain: Omega Psi Phi Fraternity responds during the Great Depression and World War II, 1930-1945 -- Safeguarding civil rights: Omega men and the postwar fight for racial equality, 1946-1959 -- Bloody but unbowed: Omega Psi Phi Fraternity during modern civil rights movement, 1960-1969 -- Keeping our lamps trimmed and burning: critical crossroads in Omega Psi Phi Fraternity, 1970-1989 -- Holding aloft vistas of purple and gold: Omega Psi Phi Fraternity, 1990 to the present.
Includes bibliographical references and index.
Maurice J. Hobson is associate professor of Africana studies and historian at Georgia State University. Eddie R. Cole is professor of education and history at UCLA and fellow at the Harvard Radcliffe Institute. Jim C. Harper II is associate dean of the School of Graduate Studies and professor of history at North Carolina Central University. Derrick P. Alridge is professor of education at the University of Virginia.
Professional and scholarly.
Print version record.
JSTOR
Keywords: Omega Psi Phi Fraternity -- History; African American Greek letter societies; African American college students -- Political activity; Civil rights movements -- United States -- History -- 20th century; Associations désignées par des lettres grecques noires américaines.; Mouvements des droits de l'homme -- États-Unis -- Histoire -- 20e siècle.; African American Studies; History; EDUCATION; 20th Century; United States; Ethnic Studies; SOCIAL SCIENCE; Electronic books